FIRST EXPERIENCE IN VIDEOURODYNAMIC STUDY AT CIPTO MANGUNKUSUMO HOSPITAL IN 2012-2014 - Tambunan, Nicholas Albert; Rahardjo, Harrina E (Indonesian Urological Association, 2019)
Objective: Accuracy of diagnosis is a fundamental thing in terms of plan of treatment. Nowadays, symptoms from lower urinary tract can be diagnosed accurately with videourodynamic study (VUDS). Videourodynamic combines a fluoroscopic voiding cystourethrogram with multichannel urodynamics, allowing anatomic and functional assessment of the bladder and outlet. Material & Methods: This research is a descriptive retrospective. Data was taken from the patients who underwent VUDS at Department of Urology Cipto Mangunkusumo Hospital from 2012 to 2014. Patient’s characteristics were gender, age, chief complaint, working diagnosis pre investigation, and diagnosis after VUDS was performed. Then, data was analyzed in a descriptive fashion and presented using tables and narative form. Results: There were 8 male patients (67%) and 4 female (33%) who underwent VUDS. Most of the patients were children (75%). Five patients (42%) complained about incontinence with or without other LUTS, only 1 patient (8%) had LUTS and disuria. Overall, working diagnosis pre investigation was neurogenic bladder with various causes. We found a variable diagnoses after VUDS. At filling phase, we found 7 patients (58%) with small bladder capacity, 5 patients (42%) with low bladder compliance then followed respectively by overflow incontinence (33%), detrusor overactivity (17%) and urethral sphincter incompetence (8%). At voiding phase, the most common abnormality detected were detrusor underactivity (42%), followed by infravesical obstruction (8%). VUR was found both at filling phase (42%) and voiding phase (33%). Conclusion: VUDS could be the first choice of modality for diagnosing dysfunction of lower and upper urinary tract especially in neurogenic cases.